2017
DOI: 10.1270/jsbbs.16184
|View full text |Cite
|
Sign up to set email alerts
|

Multiple organ gigantism caused by mutation in <i>VmPPD</i> gene in blackgram (<i>Vigna mungo</i>)

Abstract: Seed size is one of the most important traits in leguminous crops. We obtained a recessive mutant of blackgram that had greatly enlarged leaves, stems and seeds. The mutant produced 100% bigger leaves, 50% more biomass and 70% larger seeds though it produced 40% less number of seeds. We designated the mutant as multiple-organ-gigantism (mog) and found the mog phenotype was due to increase in cell numbers but not in cell size. We also found the mog mutant showed a rippled leaf (rl) phenotype, which was probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 26 publications
3
44
2
Order By: Relevance
“…In multiple eudicot species that belong to the rosid order of Fabales, orthologs of the KIX and PPD proteins have been reported to negatively regulate seed pod size (Ge et al, 2016;Kanazashi et al, 2018;Li et al, 2019;Naito et al, 2017). To examine whether the KIX proteins might also have a role in determining tomato fruit size in the asterid model species tomato, we investigated whether the development of reproductive organs was affected in tomato kix8 kix9 mutants.…”
Section: Tomato Kix8 Kix9 Mutants Produce Bigger Tomato Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In multiple eudicot species that belong to the rosid order of Fabales, orthologs of the KIX and PPD proteins have been reported to negatively regulate seed pod size (Ge et al, 2016;Kanazashi et al, 2018;Li et al, 2019;Naito et al, 2017). To examine whether the KIX proteins might also have a role in determining tomato fruit size in the asterid model species tomato, we investigated whether the development of reproductive organs was affected in tomato kix8 kix9 mutants.…”
Section: Tomato Kix8 Kix9 Mutants Produce Bigger Tomato Fruitsmentioning
confidence: 99%
“…In Arabidopsis, the asymmetric cell division of meristemoids, which are precursor cells of the stomatal lineage, positively affects final leaf size and is restricted by a transcriptional repressor complex in which the co-repressor TPL is recruited to PPD2 by KIX8/KIX9 (Gonzalez et al, 2015;White, 2006). Members of this repressor complex were shown to regulate leaf size and shape in a variety of species that belong to different orders of the rosids (Ge et al, 2016;Gonzalez et al, 2015;Kanazashi et al, 2018;Li et al, 2019;Naito et al, 2017), suggesting that the repressor complex is a conserved regulator of leaf growth among rosid eudicots. Here, we demonstrate that the tomato orthologs of KIX8 and KIX9 act as TPL adaptors for PPD proteins as well and, thereby, regulate leaf growth in tomato, a model species of the asterid clade that also includes tobacco (Nicotiana tabacum), carrot (Daucus carota) and sunflower (Helianthus annuus).…”
Section: Kix8 and Kix9 Are Conserved Regulators Of Leaf Growth In Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the wild type, the MOG mutant significantly expressed larger seeds (69%), higher biomass (40%), and bigger leaves (72%), albeit with a lower number of seeds per pod (75%), number of pods per plants (76%), and number of seeds per plant (57%) ( Tomooka et al, 2010 ). A map-based cloning study of the mog locus revealed that an 8-bp deletion in exon 6 in VmPPD ( V. mungo PEAPOD ) results in the MOG phenotypes ( Naito et al, 2017 ). Knocking down the VmPPD orthologs in soybean resulted in larger seeds and leaves, but lower number of pods and seeds and lower seed yield per plant than a control soybean ( Naito et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A map-based cloning study of the mog locus revealed that an 8-bp deletion in exon 6 in VmPPD ( V. mungo PEAPOD ) results in the MOG phenotypes ( Naito et al, 2017 ). Knocking down the VmPPD orthologs in soybean resulted in larger seeds and leaves, but lower number of pods and seeds and lower seed yield per plant than a control soybean ( Naito et al, 2017 ). However, to efficiently exploit useful traits such as increased seed size in the MOG mutant in black gram breeding, additional information on the pleiotropic effect of VmPPD on traits in other background genomes needs to be determined.…”
Section: Introductionmentioning
confidence: 99%